Formulations based on Solid Lipid Nanoparticles (SLN) and Nanostructured Lipid Carriers (NLC) for cutaneous use: a review - Garcês, A. (2021)
Cutaneous use of lipid nanoparticles (solid lipid nanoparticles, SLN and nanostructured lipid carriers, NLC) has been showing promising results. These systems consist of low viscosity aqueous dispersions, being usually employed by means of semi-solid formulations with adequate consistency for skin application. This review addresses the cutaneous use of lipid nanoparticles for therapeutic and cosmetic applications. Initially, general information related to pharmaceutical semi-solid formulations is presented. Afterwards, the effects of SLN and NLC on the skin, and technological aspects related to semi-solid systems based on SLN or NLC are described. Finally, the most relevant studies related to the formulations based on SLN and NLC, for cosmetic and therapeutic applications, are reported. Notwithstanding the cutaneous use of SLN and NLC has been proposed for both local and transdermal delivery, the reported studies show promising results only for local application. In this sense, more research is required to better understanding the interaction mechanisms of lipid nanoparticles with skin lipids. Furthermore, the development of standard methods for skin experiments with nanoparticles is necessary.